Teachings, Epistemology, and Thoughts of Muhammad Bin Abdul Wahhab at-Tamimi in Islamic Law - Eko Kholistio Putro; Zaenul Mahmudi; Ali Hamdan (ISTAWA, 2021)
Muhammad bin Abdul Wahhab created a da'wah movement to purify Islamic doctrines. With this movement, he invited all Muslims to return to the Qur'an and Sunnah by the understanding of the Sahabah. This research is qualitative, using an analytical descriptive method and a normative juridical approach. This study aims to find out who Muhammad bin Abdul Wahhab was, how his doctrines, epistemology, and thoughts were in Islamic law, and how the term "Wahhabi" developed. and the results, Muhammad bin Abdul Wahhab was a very influential scholar in Saudi Arabia, especially in da'wah and Islamic law. Until now, his doctrines and thoughts have spread to various countries including Indonesia. He came from the tripe of sahabah who one of the beloved sahabah's of the messenger. His full name is Muhammad bin Abdul Wahhab bin Sulaiman bin 'Ali bin Muhammad bin Ahmad bin Rashid Al Wuhaibi At Tamimi. In the field of Islamic law, especially in the chapter on worshiping Allah, according to him, Islamic law can only be implemented and obeyed if there is a clear legal basis from the Qur'an and Sunnah by the understanding of the Companions. The term "Wahhabi" was assigned to him and his followers because of the similarity in his method of preaching with the real Wahhabi, Abdul Wahhab bin Abdurrahman bin Rustum, a Khowarij Ibadhiyah figure who lived in Morocco.